Newtown: a cultural precinct - real or imagined - Shand, Kate (My University, 2011)
The Newtown Cultural Precinct came about as one of government’s interventions to turn around Johannesburg’s Inner City degeneration as a result of big business’s migration to the North in the nineties when urban management and land use controls collapsed. Government’s approach to culture-led urban regeneration was by means of large public sector capital development. The research covers the history of the concept of Newtown as a cultural precinct and how it came into being. It explores the criteria for cultural precincts in terms of international best practice and whether Newtown meets these requirements. It determines whether what was planned for Newtown by government has been achieved, and is being implemented. A review of strategies, business plans, projects and activities related to the development of Newtown as a cultural precinct was undertaken, as were interviews with key stakeholders, in order to establish why the notion of a cultural precinct took root when it did, and whether it is a success or not.
MA, Faculty of Humanities, University of the Witwatersrand, 2011
Keywords: Newtown, Johannesburg; cultural precinct; culture; urban renewal